The use of FES as a strategy to improve upper limb function in stroke. What is missing? - Sousa, Andreia (2019)
Stroke is the main cause of adult disability that leads to significant impairment of upper limb (UL) function. However, despite the various rehabilitation strategies, only 5-20% recover completely. This data point to the need of improving stroke intervention methods.